The Factors Affecting the Farmer’s Wealth at Sei Rotan Village, Percut Sei Tuan District - Ahmad Fadlan; Annisa Ilmi Faried; Dinanti Dinanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
An examination of the variables affecting rice output and farmers' income levels serves as the driving force behind this study. One of the settlements where people live and work is this one. Using multiple linear regression methods and confirmatory factor analysis (CFA), the study aims to ascertain and assess the effects of fertilizer use, capital, productivity, land, distribution, price, demand, and consumption on farmers' income levels. One hundred farmers served as the sample size. Questionnaires were sent in order to gather data, and SPSS version 24.0 was used for data processing. According to the findings of experiments conducted using hypothesis testing, farmer income is significantly impacted by the factors of production, consumption, land, and prices. Next, the variables Farmer income is not significantly impacted by fertilizer use, demand, distribution, or capital. Four factors are suitable to influence income, according to the research's findings. The first component, productivity, has a value of 0.912; the second, consumption, has a value of 0.764; the third, land, has a value of 0.848; and the fourth, price, has a value of 0.864. The Rotated component matrix value indicates that there are eight factors. The government must work to inspire and excite the people to boost the wealth of farmers in Sei Rotan village, and it is hoped that farmers would keep increasing the productivity of their rice output.